Ways to improve teaching methods and techniques languages in higher education institutions - Djalmatova, Zamira (АКТУАЛЬНОЕ В ФИЛОЛОГИИ, 2021)
This paper examines the problems of studying the Russian language in universities. The characteristic features of the use of various methods and techniques in the process of educational and cognitive activity are analyzed.